Is Lone Hypertension a Risk Factor for More Severe COVID-19 Outcomes? - Evgeniya V. Shalaeva; Alisher К. Shadmanov; Feruza L. Azizova; Khilola T. Mirakhmedova; Franz H. Messerli; Oscar H. Franco; Hugo Saner (Ubiquity Press, 2022)
Background: Based on current evidence, it is not clear whether lone hypertension increases the risk for severe illness from COVID-19, or if increased risk is mainly associated with age, obesity and diabetes. The objective of the study was to evaluate whether lone hypertension is associated with increase mortality or a more severe course of COVID-19, and if treatment and control of hypertension mitigates this risk. Methods: This is a prospective multi-center observational cohort study with 30-day outcomes of 9,531 consecutive SARS-CoV-2 PCR-positive patients ≥ 18 years old (41.9 ± 9.7 years, 49.2% male), Uzbekistan, June 1-September 30, 2020. Patients were subclassified according to JNC8 criteria into six blood pressure stages. Univariable and multiple logistic regression was conducted to examine how variables predict outcomes. Results: The 30-days all-cause mortality was 1.18% (n = 112) in the whole cohort. After adjusting for age, sex, history of myocardial infarction (MI), type-2 diabetes, and obesity, none of six JNC8 groups showed any significant difference in all-cause mortality. However, age was associated with an increased risk of 30-days all-cause mortality (OR = 1.09, 95%CI [1.07-1.12], p < 0.001), obesity (OR = 7.18, 95% CI [4.18-12.44], p < 0.001), diabetes (OR 4.18, 95% CI [2.58-6.76], p < 0.001), and history of MI (OR = 2.68, 95% CI [1.67-4.31], p < 0.001). In the sensitivity test, being ≥ 65 years old increased mortality 10.56-fold (95% CI [5.89-18.92], p < 0.001). Hospital admission was 12.4% (n = 1,183), ICU admission 1.38% (n = 132). The odds of hospitalization increased having stage-2 untreated hypertension (OR = 4.51, 95%CI [3.21-6.32], p < 0.001), stage-1 untreated hypertension (OR = 1.97, 95%CI [1.52-2.56], p < 0.001), and elevated blood pressure (OR = 1.82, 95% CI [1.42-2.34], p < 0.001). Neither stage-1 nor stage-2 treated hypertension patients were at statistically significant increased risk for hospitalization after adjusting for confounders. Presenting with stage-2 untreated hypertension increased the odds of ICU admission (OR = 3.05, 95 %CI [1.57-5.93], p = 0.001). Conclusions: Lone hypertension did not increase COVID-19 mortality or in treated patients risk of hospitalization.